Health Care Reform: a Socialist Vision - Martha Livingston; Linnea Capps (Social Medicine Publication Group, 2024)
At first glance, it doesn't seem as though socialism and health-care reform have a whole lot to do with each other. After all, the most visible "left" position in the current discussion of health-care reform merely advocates for the government to assume the function of national insurer, leaving the delivery of health care - from its often-questionable content to its hierarchical relationships - firmly in place. As such, a single payer, Medicare-for-All insurance program is a modest, even tepid reform. Those of us on the left who have been active in the single payer movement have always seen it as a steppingstone toward health-care justice: until the question of access to care is solved, how do we even begin to address not only health care but also health inequities? How, for example, can working-class Americans, Americans of color, and women demand appropriate, respectful, humane, first-rate care when our ability to access any health-care services at all is so tightly constrained?